Analisis Literasi Digital dan Kesiapan Dakwah Digital Mahasiswa Sekolah Tinggi Ilmu Bahasa Arab Makassar - Aprianti, Farida; Sari, Hijrayanti; Rodiah; Hawariah, A. (CV Kalimasada Group, 2024)
Based on data at the beginning of January 2024,more than 70% of the Indonesian population accesses the internet every day. Internet is created to make human affairs easier. Although in reality positive and negative impacts arise from its use. In the scope of da'wah, digital mastery is a necessity to expand the impact of da'wah provided. So it is imperative for da'I and daiyah to be able to adapt to advance in technology. So, this research aims to determine the level of digital literacy and digital da'wah readiness of Stiba Makassar students. By using a qualitative approach methodology. The research results found that students' digital literacy levels were based on 4 pillars of digital literacy, namely digital skills, digital culture, digital ethics, and digital safety. On the digital skills pillar, student stability is at a low level, while on the digital safety pillar it is at a low level. In the digital culture pillar it is at a medium level, in the digital ethics pillar it is at a high level. The readiness for digital da'wah of STIBA students is not ready. As a Collage that makes da'wah as the main program in its education, it is important to play a role in increasing the digital literacy of its students in facing current developments and preparing them for roles in digital da'wah.